An Efficient Synthesis of 1, 3-Dialkylimidazole-2-Selenones. (June 2014) - Tian, Fengshou; Chen, Yahong; Wu, Lan; Li, Peng; Lu, Shiwei
An efficient method for the synthesis of 1, 3-dialkylimidazole-2-selenones involves the reaction of 1, 3-dialkylimidazole salts with selenium in the presence of potassium carbonate in ethanol or acetone under refluxing conditions to afford the products in good to excellent yields.